Hubungan Tingkat Asupan Sarapan Pagi dan Kualitas Tidur dengan Prestasi Belajar Siswa SMP Negeri 31 Medan - Nona Adila Syafitri Zein; Romiza Arika (Lembaga Pengembangan Kinerja Dosen, 2026)
Breakfast and sleep quality are important factors that can influence students’ concentration and academic achievement. This study aims to analyze the relationship between breakfast consumption levels and sleep quality with the learning achievement of students at SMP Negeri 31 Medan. This research used a quantitative method with a cross-sectional design. The study population consisted of all 192 eighth-grade students, with a sample of 88 respondents selected through simple random sampling. Breakfast intake was measured using a 3x24-hour food recall (breakfast time only), sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while learning achievement was obtained from semester exam scores in Indonesian Language and Mathematics subjects. Data analysis was carried out using the Chi-Square test with a significance level of 0.05. The results showed a significant relationship between breakfast intake and learning achievement in Indonesian Language (p=0.003) and Mathematics (p=0.000). Sleep quality was also proven to be associated with learning achievement in Indonesian Language (p=0.001) and Mathematics (p=0.000). The conclusion of this study is that having breakfast with adequate nutritional intake and maintaining good sleep quality contribute positively to improving students’ learning achievement.